STRATEGI KOMUNIKASI PEMBANGUNAN PEMERINTAH KABUPATEN ENREKANG MEMPERTAHANKAN PASAR SUDU - Harmin Hatta (Jurnal Dakwah Tabligh, 2021)
This research aims to (1) Identify the development communication strategy of the Enrekang Regency government in maintaining the Sudu Market (2) Challenges faced by the Enrekang Regency Government in maintaining the Sudu Market.This type of research uses descriptive qualitative methods with a persuasive communication approach. The data collection method used in this research is observation, in-depth interviews, and documentation. The analysis technique used is data reduction, data presentation, conclusion and verification.The results showed that the communication strategy carried out by the Enrekang Regency Government to maintain the Sudu Market were (1) instructional design strategy, (2) participant communication strategy, (3) marketing strategy. The challenges faced by the government in maintaining the Sudu Market are (1) the lack of awareness of traders to maintain cleanliness, (2) There are still traders who are unable to serve buyers well, (3) Managers are less strict about implementing regulations.